Characterization of urinary CD4+ and CD8+ T cells in kidney transplantation patients with polyomavirus BK infection and allograft rejection. Issue 5 (5th August 2014) - van Doesum, W.B.; Abdulahad, W.H.; van Dijk, M.C.R.F.; Dolff, S.; van Son, W.J.; Stegeman, C.A.; Sanders, J.S.F.
Abstract Background and objectives The objective of this study was to characterize CD4+ and CD8+ T‐cell populations in blood and urine of renal transplant patients with BK virus (BKV) infection or allograft rejection. Materials and methods Percentages and absolute numbers of CD4+ and CD8+ effector memory T‐cell subtype (TEM) and terminal differentiated T cells (TTD) in renal transplant patients with BKV infection (n = 14), with an episode of allograft rejection (n = 9), and in uncomplicated renal transplant patients with a stable kidney function (n = 12) were measured and compared using 4‐color fluorescence‐activated cell sorting. Results were correlated with the number of CD4+ and CD8+ T cells in renal biopsies. Results In patients with allograft rejection, the number of urinary CD4+ TEM and CD8+ TEM cells was significantly increased compared to patients with BKV infection or patients without complications. Positive correlation was found between the number of CD4+ and CD8+ cells in the renal biopsies and the number of CD4+ and CD8+ cells in urine. In patients with rejection, after 2 months of immunosuppressive therapy, a reduction in urinary CD8+ TEM cells was found. Conclusions CD4+ TEM and CD8+ TEM cells in urine could be a marker to distinguish allograft rejection from BKV‐associated nephropathy and to monitor therapy effectiveness in renal transplant patients with allograft rejection.